Coal facies in a Cenozoic paralic lignite bed, Krabi Basin, southern Thailand: Changing peat-forming conditions related to relative sea-level controlled watertable variations - H. I. Petersen (2018)
The Cenozoic Krabi Basin in the southern part of peninsular Thailand contains about 112. million. tons proven coal reserves. At present, coal is only produced from the Bang Mark mine located in the southern part of the basin, where the main lignite bed is 7-20. m thick. The lignite bed occurs in an overall paralic succession. The present paper investigates the depositional conditions of an approximately 8. m thick lignite bed (main seam) in the Bang Mark mine using organic petrography, including maceral ratios, and geochemistry. The results are further interpreted in a sequence stratigraphic context. The lignite is of low rank and is completely dominated by huminite indicating generally oxygen-deficient conditions in the precursor mire. Very low inertinite contents suggest rare occurrences of wildfires. The lower part of the lignite bed represents a topogenous fresh water peat mire with open water areas that in few cases may have experienced influx of saline water. The peat mire was subjected to periodic inundations and deposition of siliciclastics. Tissue preservation was relatively poor. The upper part of the lignite bed represents a slightly domed fresh water ombrogenous peat mire with a stable watertable and a balance between peat accumulation and accommodation space creation that favoured preservation of plant tissues. In general, the mire vegetation changed from less woody in the topogenous mire to more arborescent in the ombrogenous mire, where plants with suberinised wood cell walls also were more frequent. Decompacted, the lignite bed corresponds to a minimum ~. 11. m thick peat deposit that records from ~. 22,000 to 55,000. years of peat accumulation. Watertable rise in the peat mire was controlled overall by relative sea-level rise. In a sequence stratigraphic context, the lignite bed overlies a terrestrialisation surface (TeS; sensu Diessel, 2007) and the lowermost part records peat formation during a falling watertable and a decreasing accommodation/peat accumulation ratio (terrestrialisation). An accommodation reversal surface (ARS; sensu Diessel, 2007) indicates a change to paludification style of peat formation characterised by rising watertable and a high accommodation/peat accumulation ratio. Another ARS marks a gradual change to a situation with a balanced accommodation/peat accumulation ratio. The overall watertable rise throughout peat formation, but at a gradually slower rate from base to top, suggests that the lignite bed could be located in the late transgressive systems tract (TST). © 2011 Elsevier B.V.